2003
DOI: 10.1023/b:boli.0000009978.17777.33
|View full text |Cite
|
Sign up to set email alerts
|

Glycine N‐methyltransferase deficiency: A new patient with a novel mutation

Abstract: Summary:We report studies of a Greek boy of gypsy origin that show that he has severe de¢ciency of glycine N-methyltransferase (GNMT) activity due to apparent homozygosity for a novel mutation in the gene encoding this enzyme that changes asparagine-140 to serine. At age 2 years he was found to have mildly elevated serum liver transaminases that have persisted to his present age of 5 years. At age 4 years, hypermethioninaemia was discovered. Plasma methionine concentrations have ranged from 508 to 1049 mmol/L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 37 publications
7
75
0
Order By: Relevance
“…Loss of heterozygosity within the GNMT gene in the liver tissues of hepatocellular carcinoma patients has been reported, and GNMT alteration appears to be an early event in human hepatocellular carcinoma (11). GNMT is commonly diminished in human hepatoma and hepatoma cell lines (4)(5)(6)(7)(8)(9)(10); hence it is believed to be a susceptibility gene and a potential tumor suppressor for human hepatoma (11). Individuals with mutant GNMT and GNMT knockout mice showed that inactivation…”
Section: Introductionmentioning
confidence: 99%
“…Loss of heterozygosity within the GNMT gene in the liver tissues of hepatocellular carcinoma patients has been reported, and GNMT alteration appears to be an early event in human hepatocellular carcinoma (11). GNMT is commonly diminished in human hepatoma and hepatoma cell lines (4)(5)(6)(7)(8)(9)(10); hence it is believed to be a susceptibility gene and a potential tumor suppressor for human hepatoma (11). Individuals with mutant GNMT and GNMT knockout mice showed that inactivation…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the identification of several human individuals with persistent hypermethioninaemia resulted in discovery of natural mutations of GNMT as the reason for those metabolic abnormalities (Mudd et al, 2001;Augoustides-Savvopoulou et al, 2003). Although these individuals have evidence of mild liver disease they appear to be otherwise quite normal aside from their abnormal pattern of methionine metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Although his clinical presentation and routine liver tests support the thesis on a benign disorder, his plasma methionine was on three occasions above 1,000 mmol/L, which was estimated as approximate borderline for increased risk of various neurological complications related to hypermethioninemia regardless of the cause (Barić and Fowler 2014;Mudd 2011). Plasma methionine levels above 1,000 mmol/L were observed also in the third reported patient (Augoustides-Savvopoulou et al 2003). Very recent data from patients with methionine adenosyltransferase I/III deficiency (MAT I/III; OMIM 250850; E.C.…”
Section: Discussionmentioning
confidence: 72%
“…2.1.1.20) is an autosomal recessive inherited disorder of methionine metabolism ( Fig. 1), which has been reported in extenso so far in only three patients from two families (Mudd et al 2001;Augoustides-Savvopoulou et al 2003). In 2015, the fourth patient was described in an abstract (Rakic et al 2015).…”
Section: Introductionmentioning
confidence: 99%